2021
DOI: 10.3390/cryst11091046
|View full text |Cite
|
Sign up to set email alerts
|

Deep-Level Traps Responsible for Persistent Photocurrent in Pulsed-Laser-Deposited β-Ga2O3 Thin Films

Abstract: Gallium oxide (β-Ga2O3) is emerging as a promising wide-bandgap semiconductor for optoelectronic and high-power electronic devices. In this study, deep-level defects were investigated in pulsed-laser-deposited epitaxial films of β-Ga2O3. A deep ultraviolet photodetector (DUV) fabricated on β-Ga2O3 film showed a slow decay time of 1.58 s after switching off 250 nm wavelength illumination. Generally, β-Ga2O3 possesses various intentional and unintentional trap levels. Herein, these traps were investigated using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…7,9,18 The nature of the deep hole traps in question is under intense discussion. In 19 Tak et al demonstrated using temperature scanning and thermally stimulated current characterization that such traps activation energy was 0.64 eV and 1.03 eV. These values are in good agreement with our results 20 obtained in Si-doped β-Ga 2 O 3 films after high-energy proton irradiation (20 MeV, fluence 10 14 cm −2 ).…”
supporting
confidence: 92%
“…7,9,18 The nature of the deep hole traps in question is under intense discussion. In 19 Tak et al demonstrated using temperature scanning and thermally stimulated current characterization that such traps activation energy was 0.64 eV and 1.03 eV. These values are in good agreement with our results 20 obtained in Si-doped β-Ga 2 O 3 films after high-energy proton irradiation (20 MeV, fluence 10 14 cm −2 ).…”
supporting
confidence: 92%
“…Traps are localized in the band gap of the oxide film [12][13][14] and at the Ga 2 O 3 /GaAs interface. Owing to a significant mismatch between the parameters of a monoclinic Ga 2 O 3 lattice and a sphalerite GaAs lattice, a high density of surface states at the interface is expected.…”
Section: Experimental Data and Discussionmentioning
confidence: 99%
“…The same surface treatment using HCl and H 2 O 2 was used to form SCs using four different metals (Mo, Ni, W, and Au) on (100)-oriented β-Ga 2 O 3 bulk substrates grown by the Czochralski method (CZ) . In contrast to the results observed for (2̅01) β-Ga 2 O 3 SBDs, SBHs for these metals increased with the increase in metal work function value. Anomalous behavior was observed for Au SCs similar to Au SCs on (010) β-Ga 2 O 3 substrate .…”
Section: Schottky Contacts To Ga2o3mentioning
confidence: 95%
“…β-Ga 2 O 3 has a high breakdown electric field strength of 8 MV/cm and exceptional Baliga figure of merit (BFOM) and Johnson’s figure of merit (JFOM) due to ultrawide bandgap of 4.6–4.9 eV, much higher than those of SiC and GaN. β-Ga 2 O 3 has a high saturation electron velocity ( v s ) of 2 × 10 7 cm/s, which allows for high current density and high-frequency operation. , …”
Section: Introductionmentioning
confidence: 99%